Flouting Maxim in Smile Movie: A Pragmatic Study - Rima Desrifianti; Ervina C M Simatupang (Jurnal Sinestesia, 2023)
The objective of this research is to identify the types of flouting maxim and the factors of flouting maxim in Smile Movie. In this study, a qualitative approach that was descriptive was employed. The dialogue in the film Smile serves as the research's data source. Grice's theory (1975) served as the theoretical foundation for this study. Thirty instances of infractions of Grice's maxims of cooperation principles were found as a consequence of this investigation. The maxim of number comprises 9 data (30%), the maxim of quality includes 9 data (30%), and the maxim of relevance includes 11 data (36.6%) out of the total 30 data. and the manner 1 data maxim (3.4%). The characters also carry out the following factors: 14 data (46.6%) that are competitive, 1 data (3.4%) that are convivial, 7 data (23.4%) that are collaborative, and 8 data (26.6%) that are conflictive. It is evident that, at 36.6%, relevance is the most frequently violated aspect by the characters, and competitiveness is the most frequently utilized component at 46.6%.